Mass shift of σ-meson in nuclear matter - Morones Ibarra, José Rubén; Menchaca Maciel, Mónica del Carmen; Santos Guevara, Ayax; Robledo Padilla, Felipe Ángel (Indian Academy of Sciences, 2013)
The propagation of σ-meson in nuclear matter is studied in the Walecka model, by assuming that the sigma couples to a pair of nucleon–antinucleon states and to particle–hole states. The in-medium effect of σ–ω mixing is also studied. For completeness, the coupling of sigma to two virtual pions was also considered. It is found that the σ-meson mass decreases with respect to its value in vacuum and that the contribution of the σ–ω mixing effect on the mass shift is relatively small.